Quantitative Oxygen Consumption and Respiratory Activity of Meat Spoiling Bacteria Upon High Oxygen Modified Atmosphere - Kolbeck, Sandra; Reetz, Leonie; Hilgarth, Maik; Vogel, Rudi F. (Frontiers in Microbiology, 2019)
High oxygen modified atmosphere packaging is a commonly applied method to prolong the minimum shelf life of fresh (red) meats. Upon spoilage, changes of the initial oxygen concentration and microbiome composition can be observed. Thus, we classified the typical representative meat spoiling bacteria Brochothrix (B.) thermosphacta TMW2.2101 and the four lactic acid bacteria (LAB) Carnobacterium (C.) divergens TMW2.1577, C. maltaromaticum TMW2.1581, Leuconostoc (L.) gelidum subsp. gelidum TMW2.1618 and L. gelidum subsp. gasicomitatum TMW2.1619 along their oxygen consuming capacity, which can indicate the timeline of microbiome and sensorial changes. All bacteria were grown in a model system employing gas tight glass bottles containing meat simulation media and under modified atmosphere (70% O2 and 30% CO2). Oxygen concentrations of media and headspaces were monitored over time and the oxygen uptake rate (OUR) was calculated for all species. All bacteria were able to consume dissolved oxygen, with B. thermosphacta TMW2.2101 exhibiting a 31-times higher OUR per single cell in 60 hours. Furthermore, all strains showed significant growth enhancement in the presence of heme indicating respiratory activity. Comparative genomic and physiological analyses predict the activity of a respiratory chain for all species upon high oxygen atmosphere. Versatile cytochrome composition and an additional cytochrome aa3 oxidase is suggested to be responsible for the increased OUR of B. thermosphacta TMW2.2101. Furthermore, B. thermosphacta TMW2.2101 revealed highest oxidative stress tolerance compared to the other bacteria, facilitating a higher respiratory activity. Coupling of respiration and fermentation via regeneration of NADH can be a competitive advantage for meat spoiling bacteria resulting in a higher cell count and possibly accelerated spoilage. The exhibited highest capacity for oxygen consumption of B. thermosphacta compared to lactic acid bacteria in vitro also suggests a higher contribution of this bacterium to the change in the atmosphere upon spoilage of MAP meats in situ.